Semaphorin 7a aggravates TGF-β1-induced airway EMT through the FAK/ERK1/2 signaling pathway in asthma - Peng, Haiying; Sun, Fei; Jiang, Yunxiu; Guo, Zihan; Liu, Xinyi; Zuo, Anli; Lu, Degan (Frontiers in Immunology, 2023)
Background TGF-β1 can induce epithelial-mesenchymal transition (EMT) in primary airway epithelial cells (AECs). Semaphorin7A (Sema7a) plays a crucial role in regulating immune responses and initiating and maintaining transforming growth factor β1 TGF-β1-induced fibrosis. Objective To determine the expression of Sema7a, in serum isolated from asthmatics and non-asthmatics, the role of Sema7a in TGF-β1 induced proliferation, migration and airway EMT in human bronchial epithelial cells (HBECs) in vitro. Methods The concentrations of Sema7a in serum of asthmatic patients was detected by enzyme-linked immunosorbent assay (ELISA). The expressions of Sema7a and integrin-β1 were examined using conventional western blotting and real-time quantitative PCR (RT-PCR). Interaction between the Sema7a and Integrin-β1 was detected using the Integrin-β1 blocking antibody (GLPG0187). The changes in EMT indicators were performed by western blotting and immunofluorescence, as well as the expression levels of phosphorylated Focal-adhesion kinase (FAK) and Extracellular-signal-regulated kinase1/2 (ERK1/2) were analyzed by western blot and their mRNA expression was determined by RT-PCR. Results We described the first differentially expressed protein of sema7a, in patients with diagnosed bronchial asthma were significantly higher than those of healthy persons (P<0.05). Western blotting and RT-PCR showed that Sema7a and Integrin-β1 expression were significantly increased in lung tissue from the ovalbumin (OVA)-induced asthma model. GLPG0187 inhibited TGF-β1-mediated HBECs EMT, proliferation and migration, which was associated with Focal-adhesion kinase (FAK) and Extracellular-signal-regulated kinase1/2 (ERK1/2) phosphorylation. Conclusion Sema7a may play an important role in asthma airway remodeling by inducing EMT. Therefore, new therapeutic approaches for the treatment of chronic asthma, could be aided by the development of agents that target the Sema7a.